Methylene blue rejection and antifouling properties of different carbonaceous additives-based polyvinylidene fluoride membrane - Suriani Abu Bakar (Tanjung Malim, 2023)
Methylene blue rejection and antifouling properties of different carbonaceous additives-based polyvinylidene fluoride membrane by Suriani Abu Bakar